2001
DOI: 10.1001/archopht.119.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Subtypes of Stargardt Macular Dystrophy–Fundus Flavimaculatus

Abstract: To determine if phenotypic subtypes exist in Stargardt macular dystrophy-fundus flavimaculatus (SMD-FFM). Methods: A cross-sectional study of 63 patients with autosomal recessive SMD-FFM was undertaken. The age of onset, duration of symptoms, visual acuity, and clinical features on fundus examination, color fundus photographs, and fundus autofluorescence images were recorded. Electrophysiological tests, including pattern, focal, and fullfield electroretinogram (ERG), electro-oculogram, and colorcontrast sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
239
3
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(250 citation statements)
references
References 21 publications
5
239
3
3
Order By: Relevance
“…Full-field ERG provides an objective measure of peripheral retinal involvement. Three functional phenotypic subtypes were established previously 12 (see Methods) and a longitudinal follow-up of the same cohort (mean follow-up 11 years) found that only 20% of ERG group 1 (normal full-field ERG) cases had progression to either group 2 or 3 (cone and cone-rod dystrophy, respectively), whereas 100% of patients with initial rod ERG abnormality showed significant progression. The correlation between genotype and ERG is poorly understood and difficult to explore due to the genetic heterogeneity of ABCA4.…”
Section: Discussionmentioning
confidence: 99%
“…Full-field ERG provides an objective measure of peripheral retinal involvement. Three functional phenotypic subtypes were established previously 12 (see Methods) and a longitudinal follow-up of the same cohort (mean follow-up 11 years) found that only 20% of ERG group 1 (normal full-field ERG) cases had progression to either group 2 or 3 (cone and cone-rod dystrophy, respectively), whereas 100% of patients with initial rod ERG abnormality showed significant progression. The correlation between genotype and ERG is poorly understood and difficult to explore due to the genetic heterogeneity of ABCA4.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ERG group I disease had normal amplitude of the photopic and scotopic ERGs; ERG group II disease patients had relative loss of cone-driven function, while ERG group III patients had abnormally reduced scotopic and photopic ERGs. 39 With advanced STGD1, photopic and scotopic responses may become diminished below the recording threshold, whereby it becomes difficult to distinguish ERG group III disease form a rod-cone pattern of dysfunction electrophysiologically. In this situation a presenting history of nyctalopia, rather than light aversion and/or central or color vision problems, would suggest a diagnosis of RP rather than ERG group III disease.…”
Section: Electroretinogrammentioning
confidence: 99%
“…Stargardt's disease affects individuals of any age, gender and race [1,5,7]. Limit of visual acuity, fundus appearance and severity of the disease varies widely among patients [1,7,8]. Typically, fundus flecks and atrophic patches at the macula and the mid-peripheral retina are difficulties in writing and was able to write in a straight line.…”
Section: Vision Rehabilitation As Defined By American Optometricmentioning
confidence: 99%